Features of Code Switching in Bilingual Children - Dabašinskienė, Ineta; Kamandulytė-Merfeldienė, Laura (Vilnius University Open Series, 2023)
This article discusses the use of code switching for bilingual children. The aim of the study was to assess which types and functions of code switching dominate in children’s narratives collected according to the MAIN methodology. Samples of children from different language groups (LT-EN and RU-LT) were chosen as they were expected to reveal different patterns of code-switching. The study revealed that code-switching was more frequent in the RU-LT sample, whose children lived in Lithuania but grew up in Russian-speaking families and attended educational institutions for national minorities. The children lacked basic Lithuanian language skills and were more likely to use words or phrases from their mother tongue to express their thoughts. Contrary to what is reported in international studies on children’s language development, in the case of Lithuania it is evident that even in third-generation Russian-speaking families Lithuanian is rarely used. Lithuanian children living in an English-speaking country (LT-EN) had fewer difficulties in speaking Lithuanian: fewer instances of code-switching in their narratives were observed and usually they were related to narrative coherence. In the RU-LT group, there was a very clear motivation for the use of code-switching – the code-switching recorded in the narratives was related to filling lexical gaps. A completely different trend emerged in the LT-EN sample, where English words or phrases helped the children to connect the narratives and to link the structural components of the story. In summary, code-switching is used as a helping strategy for the success of the task by helping the child to tell a story in a language that is inherited by some and a second language by others. Thus, even if the child inserts words in Russian or English, he/she successfully completes the task and tells the story according to the pictures that were presented to the children.